Cytokine profile in patients with hydronephrosis transformation before and after surgery - Pavlov, S. B.; Savenkov, V. I.; Pavlova, G. B. (Journal of Education, Health and Sport, 2017)
Pavlov S. B., Savenkov V. I., Pavlova G. B. Cytokine profile in patients with hydronephrosis transformation before and after surgery. Journal of Education, Health and Sport. 2017;7(1):300-316. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.260210 http://ojs.ukw.edu.pl/index.php/johs/article/view/4200 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. CYTOKINE PROFILE IN PATIENTS WITH HYDRONEPHROSIS TRANSFORMATION BEFORE AND AFTER SURGERY S. B. Pavlov, V. I. Savenkov, G. B. Pavlova Kharkiv Medical Academy of Postgraduate Education, Kharkiv National Medical University Abstract Introduction. An Urgent problem of urology is recurrence of strictures of the ureter as a consequence of hydronephrosis. The basis of development of nephrosclerosis and scarring leading to recurrence of stricture, is the reaction of the connective tissue, the violation of dynamic equilibrium of its tissue system and the inadequacy of the reparative regeneration is determined by the functional state of the connective tissue and balance the regulatory systems at the level of intercellular mediators. The aim of this work was to study molecular mechanisms of participation of the physiological system of connective tissue and to determine the extent of its involvement in the development of the pathological process in patients with hydronephrosis through a comparative assessment of the level of cytokines and their relationships before and after surgical intervention. Materials and methods. The studied group included 174 patients with hydronephrosis of II-III stages, obstruction of the upper urinary tract of different etiology. It was studied the contents of cytokines (RANKL, OPG, IL-1RA, TGF-β1, IL-17, adiponectin and visfatine) in the serum by ELISA before surgery and for 21 days after surgery. Research results. It was established that in patients with hydronephrosis the level of RANKL after surgery did not differ from the control and level before surgery. Levels ofOPG,IL-1RA, adiponectin and visfatine before surgery was lower than in controls. After surgery, compared to the preoperative period, levels increased (with the exception of levels of adiponectin, which remained low) and become the same as in control. The level of TGF-β1 before and after the operation was higher than in controls. After surgery it did not differ from the preoperative level. The level of IL-17 before and after operation was low. Conclusion. In patients with hydronephrosis the imbalance in system of regulation of functional system of connective tissue at the level of intercellular mediators which was shown by activation of a regulatory way of RANR-RANKL-OPG due to decrease in the OPG level is observed. The revealed changes can demonstrate violation of the general scheme of regulation of processes of remodeling of connective tissue and decrease in reserves of adaptation of an organism. Restoration of a normal passage of urine as a result of surgery leads to normalization of the OPG level and elimination of an imbalance of the RANKL-RANK-OPG system and also normalization of the IL-1RA levels and a visfatin. Keywords: hydronephrosis transformation, physiological system of the connective tissue, cytokines, regulatory path